Marriage without wali in Malaysia: a socio legal study on its causes, implications & solutions - Mohd, Azizah; Hj Ibrahim, Badruddin; Abdul Razak, Syafiqah (Universiti Sultan Zainal Abidin (UNiSZA), 2017)
1. INTRODUCTION Marriage is an important institution for human production. It seems that there is no jurisdiction surrounding the world that negates this fact. This further enhances the fact that marriage is one of the crucial legal means that preserve the continuation of human generation on earth. In Islam, marriage is considered as a sacred institution that protects sanctity of lineage especially in a civilized society. This has been mentioned nicely by Zeenat in her writing that the primary base of any civilized society is when two people of different sexes are united in a perfectly lawful way. (Shaukat Ali, Zeenat.; e). Marriage celebrates the nature of human being and recognizes their feelings of love, to love, to be loved and to live in harmony and peace. Marriage is the best solution that guarantees happiness in the right way. (Mustafa Al-Khin; 2011). Nevertheless, in order to achieve a legal and blessed marital relationship, the couple have to fulfill several marriage requirements one of which is guardian or wali. Under Islamic law, guardianship (wilayah) refers to legal authority invested in a person (wali) who is fully qualified and competent to safeguard the interests and rights of another (his ward) who is incapable of doing so independently or has limited or no legal capacity. (Mustafa Al-Khin,2011). Wali is therefore, a person who in charged to manage the affairs of this person and as regards to marriage, with authority to give away a woman in marriage. (Nasution, S., 2009). Basically, the guardian in marriage is divided into general guardian (walī am) who have a general authority of guardianship over women in a Muslim territory i.e. ruler or head of state and specific guardian (walī khas), i.e. who has authority specifically on those daughters or relatives based on lineage or blood relationship. They include the father, grandfather how high so ever, the germane or consanguine brother or brothers, paternal nephews, paternal uncles and so forth from residuary group (‗asabah) of inheritance. (al- Zuhaily, 2001)